Vestibular brain changes within 70 days of head down bed rest. Issue 7 (12th March 2018) - Yuan, Peng; Koppelmans, Vincent; Reuter‐Lorenz, Patricia; De Dios, Yiri; Gadd, Nichole; Wood, Scott; Riascos, Roy; Kofman, Igor; Bloomberg, Jacob; Mulavara, Ajitkumar; Seidler, Rachael
Abstract: Head‐down‐tilt bed rest (HDBR) is frequently utilized as a spaceflight analog research environment to study the effects of axial body unloading and fluid shifts that are associated with spaceflight in the absence of gravitational modifications. HDBR has been shown to result in balance changes, presumably due to sensory reweighting and adaptation processes. Here, we examined whether HDBR results in changes in the neural correlates of vestibular processing. Thirteen men participated in a 70‐day HDBR intervention; we measured balance, functional mobility, and functional brain activity in response to vestibular stimulation at 7 time points before, during, and after HDBR. Vestibular stimulation was administered by means of skull taps, resulting in activation of the vestibular cortex and deactivation of the cerebellar, motor, and somatosensory cortices. Activation in the bilateral insular cortex, part of the vestibular network, gradually increased across the course of HDBR, suggesting an upregulation of vestibular inputs in response to the reduced somatosensory inputs experienced during bed rest. Furthermore, greater increase of activation in multiple frontal, parietal, and occipital regions in response to vestibular stimulation during HDBR was associated with greater decrements in balance and mobility from before to after HDBR, suggesting reduced neural efficiency. These findings shed light on neuroplastic changes occurring with conditions of altered sensory inputs, and reveal the potential for central vestibular‐somatosensory convergence and reweighting with bed rest.